Trauma exposure, posttraumatic stress disorder and oxytocin: a meta-analytic investigation of endogenous concentrations and receptor genotype - Engel, Sinha; Klusmann, Hannah; Laufer, Sebastian; Pfeifer, Ann-Christin; Ditzen, Beate; van Zuiden, Mirjam; Knaevelsrud, Christine; Schumacher, Sarah (Neuroscience & biobehavioral reviews, 2019)
Oxytocin’s stress-reducing and social functions suggest an involvement in trauma processing and posttraumatic stress disorder (PTSD). We searched PubMed, PubPsych, PsycINFO, PsycARTICLES, Web of Science, ProQuest and ClinicalTrials.gov for studies assessing endogenous oxytocin, oxytocin receptor genotype or methylation in traumatized humans. Eligible studies (k=66) were systematically described. We meta-analytically compared oxytocin parameters between traumatized and non-traumatized individuals (k=17) and individuals with and without PTSD (k=8), and correlated oxytocin with trauma exposure (k=16) and PTSD symptoms (k=8). Endogenous oxytocin concentrations did not differ between PTSD patients and healthy individuals. The remaining effects on endogenous oxytocin were heterogeneous. Subgroup analyses identified sampling-related, trauma-related and demographic moderators, resulting in inconsistent or non-significant effects. Methylation data were insufficient for meta-analyses, and meta-analytic genotype results were inconsistent. Unstimulated endogenous oxytocin was not a biomarker for trauma exposure or PTSD. Given the impact of methodology, more basic research on endogenous oxytocin measurements is needed. Future studies might consider the oxytocin stress response and investigate oxytocin longitudinally.
Gesehen am 18.02.2020